Moderating Role of Institutional Quality on Human Capital Development - Poverty Reduction Nexus in Nigeria: Evidence from Cointegrating Regressions - Ojeyinka, Titus A. (Ife Social Sciences Review, 2025)
At the forefront of the Sustainable Development Goals (SDGs) is the need to end poverty in all its forms by 2030. To achieve this, investment in human capital development (HCD) has been identified as a fundamental factor. In line with this, the present study seeks to investigate the economic benefit of HCD on poverty in Nigeria. The study also examines the moderating role of institutional quality in the relationship between HCD and poverty by employing the Bound test for cointegration and cointegrating regression techniques on annual data between 1990 and 2023. To complement the outcomes from the main analysis, the Granger causality test is performed on the target variables. The results from the Bound test confirm the existence of cointegration between HCD and poverty level in all the estimated models. The findings from the DOLS reveal that both education and health spending stimulate household consumption expenditure per capita and income per capita. The outcomes are consistent across different model specifications and robust to alternative estimation strategies. The findings imply that HCD reduces poverty rate suggesting that HCD is a strong driver of poverty reduction in Nigeria. Conversely, institutional quality plays a strong negative moderating role by dampening the reducing effect of HCD on poverty. This implies that the quality of the institution matters in the effectiveness of HCD on poverty reduction in Nigeria. The finding from the Ganger causality test reveals a unidirectional causality stemming from HCD components to the two indicators of poverty except for life expectancy rate and poverty metrics where a feedback causal effect is established. The study highlights key policy recommendations for Nigeria to attain the goal of poverty eradication by 2030.